Pengaruh Atraksi Budaya dan Wisata Halal Terhadap Kepuasan Wisatawan Melalui Tourist Experience di Kuta Mandalika Lombok NTB - Irwan Yon Hadi (SENTRI: Jurnal Riset Ilmiah, 2026)
Tourism is an important sector in supporting national economic development. The Mandalika Kuta Special Economic Zone (SEZ) in Central Lombok has been developed as a leading tourist destination based on sustainable tourism, cultural attractions, and halal tourism. However, despite its great potential and numerous awards in halal tourism, the number of tourist visits to Lombok declined in 2019. This condition highlights the importance of improving tourist satisfaction through high-quality travel experiences. This study aims to analyze the influence of cultural attractions and halal tourism on tourist satisfaction, with tourist experience serving as a mediating variable in the Mandalika Kuta SEZ. This research adopts a quantitative approach, with data collected through questionnaires distributed to tourists visiting Mandalika Kuta. The data were analyzed using path analysis to examine both direct and indirect relationships among variables. The results are expected to show that cultural attractions and halal tourism have a positive effect on tourist experience, which in turn significantly influences tourist satisfaction. These findings are expected to provide useful insights for destination managers and local governments in formulating tourism development strategies oriented toward enhancing tourist experience and satisfaction.